Evaluating the Bioactivity of a Novel Broad-Spectrum Antimicrobial Peptide Brevinin-1GHa from the Frog Skin Secretion of Hylarana guentheri and Its Analogues - Qi Chen; Peng Cheng; Chengbang Ma; Xinping Xi; Lei Wang; Mei Zhou; Huimin Bian; Tianbao Chen (Toxins, 2018)
Many antimicrobial peptides (AMPs) have been identified from the skin secretion of the frog Hylarana guentheri (H.guentheri), including Temporin, Brevinin-1, and Brevinin-2. In this study, an antimicrobial peptide named Brevinin-1GHa was identified for the first time by using ‘shotgun’ cloning. The primary structure was also confirmed through mass spectral analysis of the skin secretion purified by reversed-phase high-performance liquid chromatography (RP-HPLC). There was a Rana-box (CKISKKC) in the C-terminal of Brevinin-1GHa, which formed an intra-disulfide bridge. To detect the significance of Rana-box and reduce the hemolytic activity, we chemically synthesized Brevinin-1GHb (without Rana-box) and Brevinin-1GHc (Rana-box in central position). Brevinin-1GHa exhibited a strong and broad-spectrum antimicrobial activity against seven microorganisms, while Brevinin-1GHb only inhibited the growth of Staphylococcus aureus (S. aureus), which indicates Rana-box was necessary for the antimicrobial activity of Brevinin-1GHa. The results of Brevinin-1GHc suggested transferring Rana-box to the central position could reduce the hemolytic activity, but the antimicrobial activity also declined. Additionally, Brevinin-1GHa demonstrated the capability of permeating cell membrane and eliminating biofilm of S. aureus, Escherichia coli (E. coli), and Candida albicans (C. albicans). The discovery of this research may provide some novel insights into natural antimicrobial drug design.